Optimalisasi Pembelajaran Nahwu-Shorof dengan Buku Al-Miftāḥ li Al-‘Ulūm Studi di MTs Ponpes Sabiilillah Kayuagung - Robiatul Adawiyah, Siti; Wasilah, Wasilah; Prasetyo, Bambang; Mardha Tilla (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2025)
This study aims to optimize Nahwu and Shorof learning at MTs Sabiilillah Kayuagung by implementing the Al-Miftah li Al-Ulum book and measuring its effectiveness in improving student understanding. Optimization is carried out by analyzing previous learning methods and implementing a more innovative and effectiveness-based approach. This study uses a mixed methods method with a sequential exploratory design. The first phase uses qualitative methods, including observation, interviews, and documentation, to understand the learning process before implementing the new method. Next, a quantitative analysis is conducted using a pre-test and post-test with a one-group pre-test post-test design to measure the method's effectiveness. Saturated sampling techniques are used by involving all grade VIII students as research subjects. The results of the study showed that before optimization, Nahwu and Shorof learning was still dominated by lecture methods with traditional textbooks that were less interesting and effective, so that student understanding was low. After implementing the Al-Miftah li Al-Ulum book as an optimization effort, the post-test results showed a significant increase in student understanding. The N-Gain Score test confirmed a fairly high increase, and the hypothesis test showed a significant difference between the pre-test and post-test results. Thus, the optimization of learning through the Al-Miftah li Al-Ulum book has proven effective in improving students' understanding of Nahwu and Shorof. This study recommends the application of this method more widely to improve the quality of Arabic language learning at the madrasah level.